Changing Nursing Student Attitudes to Consumer Participation in Mental Health Services: A Survey Study of Traditional and Lived Experience-led Education. (1st September 2014) - Byrne, Louise; Platania-Phung, Chris; Happell, Brenda; Harris, Scott; Sci, Dip Health; Hlth Nurs, M Ment; Bradshaw, Julie
<x xml:space="preserve">Abstract</x> Mental health policy emphasises the importance of consumer participation in mental health services. To align education with policy and orient future healthcare services to active consumer involvement, the potential of academics with a lived experience of mental illness to impact on student attitudes towards consumer participation needs to be examined. A cohort comparative study was undertaken comparing attitudinal change between undergraduate nursing students undertaking two different mental health courses, one nurse-led (n = 61) and one lived experience-led. Attitudes were measured through the Mental Health Consumer Participation Questionnaire. Within-cohort change was assessed via dependent sample t-tests, and degree of change was observed in each cohort, by comparing effect sizes. For the nurse-led course, attitudes on consumer involvement t (60) = –1.79, p < 0.005 (95% CI: –2.84, –0.74) and consumer as staff t (60) = –4.12, p < 0.005 (95% CI: –3.34, –1.16), positively changed with effect size r of 0.40 and 0.47, respectively. For the lived experience-led course, attitudes on consumer capacity t (109) = –3.63, p < 0.005 (95% CI: –0.48, –1.41) and consumer as staff, t (109) = –5.63, p < 0.005 (95% CI: –0.97, –0.46), positively changed, effect size r of 0.33 and 0.47, respectively. Mental health nursing education has a positive and selective influence on attitudes to consumer participation. Lived experience-led education was more beneficial in changing attitudes to consumer capacity and both types of education had similar positive effects on attitudes to consumers as staff.